Pengaruh Kepemimpinan Terhadap Stres Kerja Pegawai Pada Dinas Pendidikan dan Kebudayaan Kabupaten Bengkulu Utara - Sumarni, Hania (SENGKUNI Journal (Social Science and Humanities Studies), 2022)
The Department of Education and Culture of North Bengkulu Regency, as an institution tasked with building and advancing education in North Bengkulu Regency, naturally has a substantial workload. The heavy workload can lead to work stress among its employees, resulting in unsatisfactory achievement of organizational goals and objectives. The purpose of this study is to determine the effect of leadership on employee work stress at the Department of Education and Culture of North Bengkulu Regency. This research is a quantitative study using an explanatory survey method. The population and sample in this study are the employees of the Department of Education and Culture of North Bengkulu Regency, totaling 48 people. The data analysis techniques used in this study include descriptive analysis and product moment analysis for partial significance testing (t-test) and the coefficient of determination (R2). The results of the study indicate that the leadership variable affects employee work stress (Y). Based on the t-test, the leadership variable has a positive and significant effect on employee work stress.